PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN DALAM PEMBERDAYAAN PARA PENGANGGURAN DI KOTA SURAKARTA - Suranto, Joko (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
Abstract Work represent one of the element from prosperity of society, so that have to always get careful attention, either from government in charge of in executing UUD commendation 1945 section 27 sentence (2) expressing, that every citizen is entitled to the competent subsistence and work to is human This matter sign, that government have obligation to provide work field for all citizen in order to fulfilling its rights referring to competent subsistence and work, as according to human aspect. In bearing that's, hence Institute Enable ness of Society Rural (LPMK) have opportunity and challenge to be powered all unemployed, so that they have high competitiveness in obtaining work or even can to create work to themselves. Keywords: Institute enable ness of society, unemployment